(untitled) (Revista Médica de Trujillo, 2022)
The story of Nicolás Alcázar, a hero doctor of the independence of Peru, is presented; the importance of their heroic acts is considered, because despite the controversy that, for some authors, the independence figures of the time are, it is recognized that these acts are based on ethical and moral principles that must be defended by doctors also in the present.